The Influence of Principals' Leadership on Teacher Performance - Sumiati Sumiati; Irawan Hadi Patanggu; Masmur M (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
This study examines the dynamics of principal leadership and its relationship with teacher performance within the framework of educational management at the elementary school level. The focus of the study is how principal leadership practices shape the quality of teacher performance at SDN 15 Rio Pakava and SDN 8 Rio Pakava, Donggala Regency. This study employed a quantitative approach with a correlational design. Data were collected through questionnaires, structured observations, and documentation involving all 22 teachers as research respondents. Hypothesis testing was conducted using simple linear regression analysis. The results showed that principal leadership had a positive and significant effect on teacher performance, with a significance value of 0.000 < 0.05 and a regression coefficient of 0.806. The coefficient of determination (R²) of 0.869 indicates that principal leadership contributed 86.9% to the variation in teacher performance. This study emphasizes the importance of strengthening principal leadership as a strategy to improve the quality of basic education and teacher performance.